Translation and adaptation of the Child Posttraumatic Cognitions Inventory (cPTCI) to Brazilian Portuguese - Lobo,Beatriz de Oliveira Meneguelo (2014)
Introduction: Experiencing a traumatic event is a risk factor for the development of mental illness, especially posttraumatic stress disorder. A child's appraisals of a traumatic event may play a prominent role in the development or maintenance of the disorder. Therefore, subjective responses should be evaluated to understand the impact of a traumatic event on a child's life. This study translated and adapted the Child Posttraumatic Cognitions Inventory (cPTCI) for use in linguistic and cultural contexts in Brazil.Methods: The process included translation, back-translation, language expert evaluation and expert committee's evaluation.Results: Content validity index scores were good for all dimensions after evaluation by two judges and one reformulation. The back-translation of the final version also showed that the cPTCI items in Brazilian Portuguese maintained the same meanings of the original in English. This version was tested in a sample of the target population, and all the items were above the cut-off point (minimum = 3.6; maximum = 4.0).Conclusions: This study was successful in producing a Brazilian version of the cPTCI. Further studies are underway to examine the reliability and the factorial and concurrent validity of cPTCI subscales.